Testing the combinatory use of PARP1 and RPA inhibitors in breast cancer cell lines - Magro, Tatiana Natália Tavares (2019)
Loss of tumor suppressor BRCA2 is strongly associated to breast cancer. BRCA2 is essential to homologous recombination (HR), which is a DNA repair pathway crucial to genomic stability. When cells become mutant for BRCA2, they cannot repair DNA damage through homologous recombination, which is an accurate repair pathway, and instead, rely on alternative error-prone pathways for DNA repair. Tumor cells mutant for BRCA2 become therefore dependent on these alternative repair pathways for survival. The most recent generation of targeted therapies for breast cancer is PARP1 inhibitors. PARP1 is a protein essential to the initiation of several DNA repair pathways, including those alternative repair pathways, like the non-homologous end joining (NHEJ). The use of these inhibitors compromises the alternative pathways leading to tumor cell death. Though tumor cells mutant for BRCA2 are particularly sensitive to PARP1 inhibitors, the onset of tumor resistance has been frequently observed after long-term treatments. This motivated us to find alternative proteins whose inhibition specifically impaired, similar to PARP1, tumor cells viability and/or growth. It was recently reported that BRCA2 regulates RNA polymerase II transcription and prevents the formation of R-loops, which are 3-strand nucleic acid structures composed of DNA:RNA hybrids. Accumulation of these R-loops is implicated in the process of carcinogenesis due to the accumulation of single-stranded DNA (ssDNA) and increased genomic instability. RPA is a ssDNA-binding protein whose function is crucial to protect ssDNA and avoid forming secondary structures, being crucial to DNA replication and DNA repair. Our objective is to identify novel druggable targets whose inhibition can be used in combination or as an alternative to PARP1 inhibitors, minimizing tumor resistance risk. Our working hypothesis is that combinatory inhibition of PARP1 and RPA will specifically increase the loss of breast cancer cells viability.